Drosophila as a Model to Study the Relationship Between Sleep, Plasticity, and Memory - Dissel, Stephane (Frontiers in Physiology, 2020)
Humans spend nearly a third of their life sleeping, yet, despite decades of research the function of sleep still remains a mystery. Sleep has been linked with various biological systems and functions, including metabolism, immunity, the cardiovascular system and cognitive functions. Importantly, sleep appears to be present throughout the animal kingdom suggesting that it must provide an evolutionary advantage. Among the many possible functions of sleep, the relationship between sleep and cognition has received a lot of support. We have all experienced the negative cognitive effects associated with a night of sleep deprivation. These can include increased emotional reactivity, poor judgment, deficit in attention, impairment in learning and memory, and obviously increase in daytime sleepiness. Furthermore, many neurological diseases like Alzheimer’s disease often have a sleep disorder component. In some cases, the sleep disorder can exacerbate the progression of the neurological disease. Thus, it is clear that sleep plays an important role for many brain functions. In particular, sleep has been shown to play a positive role in the consolidation of long-term memory while sleep deprivation negatively impacts learning and memory. Importantly, sleep is a very plastic behavior that is adapted to an individual’s need and influenced by many external and internal stimuli. For example, sleep is very different in migratory birds depending on whether they are flying or on land. In addition to being a plastic behavior, sleep can also modulate plasticity in the brain at the level of synaptic connections between neurons and neuronal plasticity influences sleep. Understanding how sleep is modulated by internal and external stimuli and how sleep can modulate memory and plasticity is a key question in neuroscience which has huge potential therapeutic benefits. In order to address this question, several animal models have been developed. Among them, the fruit fly Drosophila melanogaster with its unparalleled genetics has proved to be extremely valuable. In addition to sleep, Drosophila has been shown to be an excellent model to study many complex behaviors, including learning and memory. This review describes our current knowledge of the relationship between sleep, plasticity and memory using the fly model.